The co-creation of multi-agent social innovations: a bridge between service and social innovation research - Windrum, Paul; Schartinger, Doris; Rubalcaba, Luis; Gallouj, Faïz; Toivonen, Marja (Emerald, 2016)
Purpose: The research fields of service innovation and social innovation have, until now, been largely disconnected. At the most basic level, a great many social innovations are services, often public sector services with social entrepreneurs organizing and delivering service innovations. As well as this overlap in the focus of research, scholars in both research fields address socio-economic concerns using multidisciplinary perspectives. The purpose of this paper is to provide a framework that can bridge the two research fields. Design/methodology/approach: Inter-linkages between service and social innovation are shown by identifying research areas in which both find a joint heuristic field. This approach has been illustrated in a set of case studies in the health sector in Europe. Findings: The bridge between social innovation and service innovation research can be built when social innovation is examined through a multi-agent framework. The authors focus on social innovations where the co-creation of novel services is guided by the prominent position taken by citizens, social entrepreneurs or third sector organizations (NGOs or charities) in the innovation process. Of particular interest are the ways in which the interests of individual users and citizens are “represented” by third sector organizations. Practical implications: The case study of the Austrian nationwide public access defibrillation programme provides an exemplar of the process of co-creation by which this social innovation was developed, implemented and sustained. Here the Austrian Red Cross acted on behalf of citizens, organizing an innovation network capable of creating both the demand and the supply side of a sustainable market for the production and safe application of portable automated external defibrillators (AEDs) in Austria. This process involved, first, raising public awareness of the need for portable defibrillators and acting as a user representative when inducing changes in the design of portable AEDs. Later, there was the institutionalization of AED training in every first aid training in Austria, work with local manufacturers to produce this device, and with large user organizations to install AEDs on their premises. Originality/value: The paper develops multi-agent model of innovation that enables one to synthesize key concepts in social and service innovation literatures and, thereby, examine the dynamics of invention and diffusion of social innovations.